Operator inequalities involving Khatri-Rao Sums and Moore-Penrose inverses - Arnon Ploymukda; Pattrawut Chansangiam (My University, 2017)
We establish relations between the Khatri-Rao sum of Hilbert space operators and ordinary products, powers, ordinary inverses, and Moore-Penrose inverses in terms of inequalities. In particular, such relations hold for the tensor sum of operators and the Khatri-Rao sum of complex matrices.
Keywords: Operator (biology); MoorePenrose pseudoinverse; Matrix Theory and Algorithms